Development of dual functional converter for drive and charging power conversion for EV drive - Tadivaka, Teja Sreenu; Kumar, Malligunta Kiran; Teja, Srungaram Ravi; Reddy, Ch. Rami (Institute of Advanced Engineering and Science, 2025)
The adaptability of electric vehicle drives is primarily concerned with the size and efficiency of power conversion. This paper presents a unified power converter for the drive and charge functions of brushless direct current-based electric vehicle drives (BLDC). The symmetrical utilization of BLDC phase windings during charging operation is implemented for efficient power conversion. The unified converter operation, configuration, and control are presented. The proposed converter is simulated in the MATLAB/Simulink platform. The performance is evaluated using operational variables such as voltage, current, torque, and speed. A comparative study is presented regarding the size and efficiency of the proposed and existing drives. The proposed drive achieved 0.01 p.u. ripple in torque, 10-sec transient time for a change in speed full throttle command, and unity power factor current for charging operation, proving its robustness over the comparable drives.